Civil engineering procedure (Thomas Telford, 2009)
The sixth edition of this established guide provides a comprehensive and accessible introduction to the key project stages from conception through to completion of construction and then beyond to handing over the resulting structures and services for use.
At foot of title: ICE.
Keywords: Engineering -- Management.; elektronické knihy; electronic books